Clinical variables associated with Family Adaptability and Cohesion in patients with spinal cord injury - Neciosup-Tomé, Verónica (2020)
Background: Living with a person with a spinal cord injury affects the family environment and context, especially due to the degree to which the patient depends on the family members. The present study, descriptive and comparative, examined the association between the clinical variables to family functioning in patients with Spinal Cord Injury. Method: The sample was constituted by 100 patients of the National Institute of Rehabilitation, most were males (77%). Results: There were no statistically significant differences in family cohesion and adaptability in terms of clinical variables (etiology of the lesion, level of the lesion, type of lesion and time of evolution). A small effect size was found in terms of family adaptability and time of evolution of the lesion (d = 0.36). Conclusion: Initially, families, who live with a patient with spinal cord injury, present difficulties regarding family cohesion and adaptability. However, as time goes by, families tend to adapt to a new condition.